Management of Postpancreatectomy Hemorrhage Following Pancreaticoduodenectomy at a Tertiary Care Center in Nepal - Subedi, Nirajan; Kandel, Bishnu; Ghimire, Bikal; Kansakar, Prasan BS; Bhandari, Ramesh S; Joshi Lakhey, Paleswan (Journal of Institute of Medicine Nepal, 2020)
Introduction Postpancreatectomy hemorrhage (PPH) is an important complication which significantly increases morbidity and mortality following pancreaticoduodenectomy (PD). This study aims to find the incidence, classification, management, and mortality associated with PPH following PD. This study also describes the changes in management and outcomes between the period of 2004-2014 and 2015-2019 in our institute as in the later time period there was use of CT angiography and interventional radiology (IR) to identify and control the bleeding site.MethodsThis is a retrospective study in which medical records of patients having PPH following PD between 2004-2019 were analyzed. The grading and classification were done according to the International Study Group of Pancreatic Surgery (ISGPS). Management and outcomes were analyzed using standard descriptive statistics.ResultsA total of 43 patients developed PPH out of 336 PDs. Out of 43 patients, 4 (9.3%) had Grade A, 16 (37.2%) had Grade B and 23 (53.5%) had Grade C PPH. Fifteen (35%) patients were managed conservatively, seven (16.2%) with IR procedure and 21 (48.8%) were reexplored. There were 16 (37.2%) mortalities, out of different factors- intraoperative blood loss >500 ml showed the predictability for mortality (p= 0.01). On comparing two time periods it was seen that the PPH rate was almost similar but the mortality decreased from 58.8% to 23.07%.ConclusionPPH following PD is associated with high mortality. Increased use of IR procedure and CT angiography can decrease the relaparotomy rates and eventually decrease mortality.